Variation of PEAR1 DNA methylation influences platelet and leukocyte function - Izzi, Benedetta (Clin Epigenetics, 2019)
BACKGROUND: Platelet-endothelial aggregation receptor 1 (PEAR-1) is a transmembrane receptor involved in platelet activation and megakaryopoiesis whose expression is driven by DNA methylation. PEAR1 variants were associated with differential platelet response to activation and cardiovascular outcomes. We aimed at investigating the link between PEAR1 methylation and platelet and leukocyte function markers in a family-based population. RESULTS: We measured PEAR1 methylation in 605 Moli-family participants with available blood counts, plasma P-selectin and C-reactive protein, whole blood platelet P-selectin, and platelet-leukocyte mixed conjugate measurements. We performed principal component analysis (PCA) to identify groups of highly correlated CpG sites. We used linear mixed regression models (using age, gender, BMI, smoking, alcohol drinking, being a proband for family recruitment, being a member of myocardial infarction (MI) family as fixed effects, and family as a random effect) to evaluate associations between PEAR1 methylation and phenotypes. PEAR1 methylation Factor2, characterized by the previously identified megakaryocyte-specific CpG sites, was inversely associated with platelet-monocyte conjugates, P-selectin, and WBC counts, while positively associated with the platelet distribution width (PDW) and with leukocyte CD11b and L-selectin. Moreover, PEAR1 Factor2 methylation was negatively associated with INFLAscore, a low-grade inflammation score. The latter was partially mediated by the PEAR1 methylation effect on platelet variables. PEAR1 methylation association with WBC measurements and INFLAscore was confirmed in the independent cohort FLEMENGHO. CONCLUSIONS: We report a significant link between epigenetic signatures in a platelet functional gene and inflammation-dependent platelet function variability measured in two independent cohorts.